2022
DOI: 10.3389/fnut.2022.1004288
|View full text |Cite
|
Sign up to set email alerts
|

Association of nutrition knowledge, practice, supplement use, and nutrient intake with strength performance among Taekwondo players in Nepal

Abstract: BackgroundOptimum dietary intake and adequate nutritional knowledge have been recognized as the key factors that play a critical role in improving the athlete's health and nutrition status. This study aimed to measure the association of nutritional knowledge, practice, supplement use, and nutrient intake with strength performance among Nepalese Taekwondo players.MethodsBetween August 2019 and January 2020, a cross-sectional study was conducted among 293 Taekwondo players in Kathmandu Metropolitan City (mean ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 50 publications
1
5
0
Order By: Relevance
“…Ozsari, Kara & Kara (2021) observed similar relationships in athletes across various disciplines, demonstrating that increased knowledge and positive nutrition attitudes correlate with enhanced mental toughness. Sunuwar et al (2022) also found a positive correlation between nutritional knowledge and athletic performance in taekwondo athletes, further reinforcing the notion that dietary awareness and healthy eating practices contribute to both mental and physical well-being in athletes. Research findings by Rampersaud et al (2005) showed that a healthy diet can improve cognitive function.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Ozsari, Kara & Kara (2021) observed similar relationships in athletes across various disciplines, demonstrating that increased knowledge and positive nutrition attitudes correlate with enhanced mental toughness. Sunuwar et al (2022) also found a positive correlation between nutritional knowledge and athletic performance in taekwondo athletes, further reinforcing the notion that dietary awareness and healthy eating practices contribute to both mental and physical well-being in athletes. Research findings by Rampersaud et al (2005) showed that a healthy diet can improve cognitive function.…”
Section: Discussionsupporting
confidence: 69%
“…Previous work in this field highlights the crucial role of nutritional knowledge in influencing athletic success. Davar (2012) and Sunuwar et al (2022) emphasize the importance of accurate nutritional knowledge as a fundamental determinant of athletic achievement. Teo, Burns & Kawabata (2022) provide empirical support for this notion, demonstrating a positive correlation between netball players’ level of nutrition knowledge and their feeding behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Bakhtiar et al [ 23 ] revealed 57.3% satisfactory nutrition knowledge among adolescent trainee athletes in Bangladesh. Sunuwar et al [ 42 ] found over half Nepalese Taekwondo players with poor nutrition knowledge. Kathure et al [ 43 ] indicated that most elite athletes in Kenya had adequate nutrition knowledge (above 50%).…”
Section: Discussionmentioning
confidence: 99%
“…However, in the study by Shakeel et al [ 39 ], the actual practices of the participants were poor and did not align with their good knowledge and attitude level; only about 57.4% of the students implemented their knowledge in their practices, suggesting a gap between knowledge and behavior. Sunuwar et al [ 42 ] also indicated a poor level of nutrition practice (55.3%) in Taekwondo athletes in Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…The field of sports nutrition has seen the publication of numerous new research papers, accompanied by the release of 17 fresh consensus statements and recommendation papers from authoritative organizations such as the IOC, ACSM, and ISSN ( 2 , 20 , 23 25 ). However, there is a recurrent observation of suboptimal adherence to sports nutrition guidelines among athletes ( 26 28 ).…”
Section: Introductionmentioning
confidence: 99%